Does aid availability affect effectiveness in reducing poverty? - François Bourguignon; Jean-Philippe Platteau (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
This paper addresses the issue of the impact of aid supply on aid effectiveness. We proceed in two steps. First, we review research works that deal with the problem of governance in donor-recipient relationships and are susceptible of highlighting effects of aggregate aid availability. Second, we provide a conceptual framework that explicitly incorporates a trade-off between considerations of needs and governance. We examine the impact of aid supply on the manner in which a donor agency allocates the available money between countries differing in terms of both needs and domestic governance. The central conclusion is that a donor's utility function that embodies the need-governance trade-off and the associated optimization mechanism yield a meaningful rule to guide inter-country allocation of aid resources.
Keywords: O11; O17; O19; O43; 330; aid effectiveness; aid allocation; governance; elite capture; monitoring; Entwicklungshilfe; Allokationseffizienz; Governance-Ansatz